2016
DOI: 10.1371/journal.pone.0165257
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sialidase in Long-Term Potentiation at Mossy Fiber-CA3 Synapses and Hippocampus-Dependent Spatial Memory

Abstract: Sialic acid bound to glycans in glycolipids and glycoproteins is essential for synaptic plasticity and memory. Sialidase (EC 3.2.1.18), which has 4 isozymes including Neu1, Neu2, Neu3 and Neu4, regulates the sialylation level of glycans by removing sialic acid from sialylglycoconjugate. In the present study, we investigated the distribution of sialidase activity in rat hippocampus and the role of sialidase in hippocampal memory processing. We previously developed a highly sensitive histochemical imaging probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Minami et al . developed a highly sensitive histochemical imaging probe for sialidase activity, BTP3-Neu5Ac, which is cleaved by all 4 neuraminidases and demonstrated that, at neutral pH, the probe stained mossy fiber terminal fields in rat hippocampal acute slices [ 100 ]. The authors further showed that neuraminidase inhibitor DANA significantly impaired LTP at mossy fiber-CA3 pyramidal cell synapse.…”
Section: Rapid Changes In Cerebral Neuraminidase Activity Associated mentioning
confidence: 99%
“…Minami et al . developed a highly sensitive histochemical imaging probe for sialidase activity, BTP3-Neu5Ac, which is cleaved by all 4 neuraminidases and demonstrated that, at neutral pH, the probe stained mossy fiber terminal fields in rat hippocampal acute slices [ 100 ]. The authors further showed that neuraminidase inhibitor DANA significantly impaired LTP at mossy fiber-CA3 pyramidal cell synapse.…”
Section: Rapid Changes In Cerebral Neuraminidase Activity Associated mentioning
confidence: 99%
“…Measurements of sialidase activity. Sialidase activity was measured according to the procedure described previously 7,41 . Briefly, INS-1D cells or C6 rat glioma cells stably expressing the rat sialidase isozyme Neu3 were lysed in n-octyl-β-D -glucoside buffer.…”
Section: Methodsmentioning
confidence: 99%
“…For Neu1, some studies suggested a C-terminal transmembrane domain, whereas other studies excluded a transmembrane region proposing a lipid anchor 75,76 . Subcellular location and activity of sialidases might differ depending on the physiological conditions and the cell types, as demonstrated by the polysialic acid processing by Neu1 77 and the involvement of Neu4 in hippocampal memory processing 78 .…”
Section: Identified Sialidases and Sialyltransferases In Synaptosomesmentioning
confidence: 99%